Testing asteroseismology with Gaia DR2: hierarchical models of the Red Clump. Issue 3 (18th April 2019) - Hall, Oliver J; Davies, Guy R; Elsworth, Yvonne P; Miglio, Andrea; Bedding, Timothy R; Brown, Anthony G A; Khan, Saniya; Hawkins, Keith; García, Rafael A; Chaplin, William J; North, Thomas S H
Abstract: Asteroseismology provides fundamental stellar parameters independent of distance, but subject to systematics under calibration. Gaia DR2 has provided parallaxes for a billion stars, which are offset by a parallax zero-point (ϖzp ). Red Clump (RC) stars have a narrow spread in luminosity, thus functioning as standard candles to calibrate these systematics. This work measures how the magnitude and spread of the RC in the Kepler field are affected by changes to temperature and scaling relations for seismology, and changes to the parallax zero-point for Gaia . We use a sample of 5576 RC stars classified through asteroseismology. We apply hierarchical Bayesian latent variable models, finding the population-level properties of the RC with seismology, and use those as priors on Gaia parallaxes to find ϖzp . We then find the position of the RC, using published values for ϖzp . We find a seismic temperature-insensitive spread of the RC of${\sim }0.03\, \rm mag$ in the 2MASS K band and a larger and slightly temperature-dependent spread of${\sim }0.13\, \rm mag$ in the Gaia G band. This intrinsic dispersion in the K band provides a distance precision of${\sim } 1{{\ \rm per\ cent}}$ for RC stars. Using Gaia data alone, we find a mean zero-point of$-41± 10\, μ \rm as$ . This offset yields RC absolute magnitudes of −1.634 ± 0.018 in K and 0.546 ± 0.016 in G . Obtaining these same values through seismology would require a global temperature shift of${\sim }-70\, K$, which is compatible with known systematics in spectroscopy.